2021
DOI: 10.1055/s-0041-1731963
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Foreign Bodies in Prison Inmates

Abstract: Objective Gastric foreign bodies are a common problem brought to an endoscopist. Prisoners are more prone to ingesting unusual foreign bodies for a secondary gain. The objective of this study was to study the profile of foreign body ingestion among the prisoners brought to a tertiary care center. Methods This is a retrospective case series. All the prisoners brought for endoscopic removal of foreign bodies between January 2018 to December 2019 were included in the analysis. Patients’ baseline characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Foreign body ingestions (FoBIs) are encountered in our clinical practice, especially in the emergency [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…Foreign body ingestions (FoBIs) are encountered in our clinical practice, especially in the emergency [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…FBI in adult patients is not very common and it is usually reported in psychiatric patients and prisoners [ 1 ]. Intentional FBI among prisoners can be seen commonly for secondary gain, for example, it was reported that 1 out of 1900 inmates in the Ohio state had FBI [ 2 ]. Most of FBI cases can be managed conservatively without intervention, only 10 to 20% of the cases would need endoscopic retrieval [ 1 ].…”
Section: Introductionmentioning
confidence: 99%